Home School Community Liaison Coordinators (HSCL) perspectives on supporting family wellbeing and learning during the Covid-19 school closures: critical needs and lessons learned. Issue 2 (3rd April 2021) - Ross, Colman; Kennedy, Maria; Devitt, Ann
Abstract : Home School Community Liaison Coordinators (HSCLs) play an essential role in the Irish education system to address systemic educational disadvantage by supporting children and families. This paper focuses on the experiences of HSCLs during Covid-19 school closures in Ireland in 2020. Research questions focus on challenges and enablers for HSCLs in supporting families during the shutdown and the impact of a whole school response on remote learning. Findings highlight the pivotal role of HSCLs in supporting the wellbeing of children and families. This involves the identification of basic and learning-related needs and engagement in coordinating with the school community and external agencies to respond to those needs. In this study, addressing basic critical needs was identified as the prerequisite to supporting home learning. The internal organisation and strategy of individual schools promoting a whole school approach to wellbeing and home-schooling was highlighted as key to successful support mechanisms. Recommendations highlight the importance of establishing and provisioning appropriate communication approaches with families in order for HSCLs to fulfil their role. Crucial here was the benefit of real physical contact as well as digital means. This has clear implications for public health guidance for schools in adopting holistic approaches to support families.